The Impact of Using Artificial Intelligence on Public Services in Indonesia - Yaya Mulyana (GoAcademica Research & Publishing, 2023)
The development and advancement of technology are entering a new father, where almost all aspects of life are using and utilizing technology a lot. The presence of technology aims to make it easy for users to meet human needs in activities and also provide comfort to its users. Dynamic technological advances demand government readiness to balance these developments; using and applying artificial intelligence (Artificial intelligence/AI) in public service is possible because it will increase public trust in the government. This study uses a qualitative approach and descriptive method, which aims to describe social phenomena that occur in society, which are then collected and analyzed to describe and describe existing phenomena, both natural and human-made, which pay more attention to characteristics, quality, and interrelationships between activities.